Associations of metabolic heterogeneity of obesity with depression progression among middle-aged and older adults in China: a prospective study - Huang, Li; Liao, Chengcheng; Liang, Zhenzhen; Chen, Huajian (Journal of affective disorders, 2025)
Background - In previous studies, there have been few studies focusing on the association between metabolic heterogeneity of obesity and depression. The association between metabolic heterogeneity of obesity and depression progression remains unclear. - Methods - This study used data from the China Health and Retirement Longitudinal Study (CHARLS) from 2011 to 2018. Metabolic heterogeneity of obesity was assessed according to four obesity and metabolic statuses, namely metabolically healthy normal weight (MHNW), metabolically unhealthy normal weight (MUNW), metabolically healthy overweight/obesity (MHOO) and metabolically unhealthy overweight/obesity (MUOO). Linear mixed-effects models were used to analyze the association between metabolic heterogeneity of obesity and depression progression. - Results - After 7 years of follow-up, MUNW, MHOO, and MUOO showed accelerated depression progression compared with MHNW, with additional annual increases of 0.09 (95 % CI: 0.02 to 0.17), 0.12 (95 % CI: 0.03 to 0.20), and 0.10 (95 % CI: 0.04 to 0.17). Participants with stable MUNW, MHOO, MUOO, MHNW transition to MUNW, and weight change in metabolically abnormal states exhibited accelerated depression progression compared to stable MHNW. And accelerated depression progression was significant in MUNW, MHOO, and MUOO among participants without social activities. - Conclusions - Although MUNW, MHOO, and MUOO exhibited milder depressive symptoms at baseline compared to MHNW, these phenotypes were associated with an accelerated depression progression over time. Additionally, social activities can mitigate the acceleration of depression progression. Our findings highlighted the important role of obesity and metabolic status and their shifts in the depression progression in middle-aged and older adults, and emphasized the buffering role of positive social activities.